COMMITMENT TO HIV/AIDS PREVENTION BEHAVIOR AND IT’S FACTOR AMONG INDONESIAN YOUTH: A CROSS-SECTIONAL STUDY - Widayati, Dhina (Indonesian Journal of Community Health Nursing, 2026)
Introduction: HIV/AIDS is a terminal disease that attacks the immune system with a fairly high incidence in Indonesia. Adolescents are one of the groups at risk of this, so a commitment is needed in preventing this disease. The purpose of this cross-sectional study was to determine the commitment of adolescents in HIV/AIDS prevention behavior and identify factors that influence it.   Method: This cross-sectional study involved 102 adolescents through total sampling. Independent variables include demographic factors (age, gender and residential status) and perception of benefits measured using a questionnaire. The commitment variable as the dependent variable was measured using a questionnaire containing 9 questions. Data were analyzed univariately and bivariately with a significance level of 0.05 by the Spearman Rank test.   Result: The results of the study showed that most respondents (56.9%) had a good commitment in HIV/AIDS prevention behavior. Factors that influence commitment include: gender (p =<0.001) and perception of benefits (p=<0.001). Age and residence status were not related to prevention commitment with p=0.224 and p=0.081. Adolescents who have a positive perception of the benefits of carrying out disease prevention behaviors and know the dangers of HIV/AIDS are more committed to adopting prevention behaviors. Gender (woman) is also an important determinant in prevention commitment because of health awareness, exposure to sexual education, and the role of maintaining reproductive health.   Conclusion: Schools have a role in increasing commitment to HIV/AIDS prevention through optimizing educational and counseling facilities with a gender-based prevention approach and focusing on increasing perceptions of benefits.   Keywords: Adolescents, commitment, HIV /AIDS, preventive behavior, perceived benefit